High-degree atrioventricular block complicating ST segment elevation myocardial infarction in the contemporary era. Issue 1 (11th December 2015) - Auffret, Vincent; Loirat, Aurélie; Leurent, Guillaume; Martins, Raphael P; Filippi, Emmanuelle; Coudert, Isabelle; Hacot, Jean Philippe; Gilard, Martine; Castellant, Philippe; Rialan, Antoine; Delaunay, Régis; Rouault, Gilles; et al.
Abstract : Background: High-degree atrioventricular block (HAVB) is a common complication of ST segment elevation myocardial infarction (STEMI). HAVB in STEMI is historically considered as a marker of worse outcome but overall data about HAVB in the contemporary era of mechanical reperfusion and potent antiplatelet therapies are scarce. Aim: Analysing incidence, clinical correlates and impact on inhospital outcomes of HAVB in a large prospective registry (Observatoire Régional Breton sur l'Infarctus, ORBI) of modern management of STEMI with a special focus on potential differences between patients with HAVB on admission and those who developed HAVB during hospitalisation. Methods: All patients enrolled in ORBI between June 2006 and December 2013 were included in the present analysis and were divided into 3 groups: patients without HAVB at any time, patients with HAVB on admission and those who developed HAVB during hospitalisation. Results: A total of 6662 patients (age: 62.0 (52.0–74.0) years; male: 76.3%) were included in the present analysis. HAVB was documented in 3.5% of patients, present on admission in 63.7% of patients and occurring during hospitalisation in 36.3%. Patients with HAVB on admission or occurring during the first 24 h of hospitalisation had higher inhospital mortality rates (18.1% and 28.6%, respectively) than patients without (4.5%) or with HAVB occurring beyond the first 24 h of hospitalisation (8.0%). However by multivariable analysis, HAVB was not independently associated with inhospital mortality contrarily to age, presentation as cardiac arrest, anterior STEMI location, reperfusion therapy, cardiogenic shock, mechanical ventilation and occurrence of sustained ventricular tachyarrhythmias or mechanical complication. Conclusions: Patients with HAVB had a higher mortality rate than patients without. However HAVB is not an independent predictor of inhospital mortality.